Difference between Hypertrophic Pyloric Stenosis in Child with History of Prematurity and Aterm - Farid I Hussein; Yusri Dianne Jurnalis (HM Publisher, 2022)
Background: Hypertrophic pyloric stenosis (HPS) is an acquired condition in which the circumferential muscle of the pyloric sphincter becomes thickened, resulting in elongation and obliteration of the pyloric channel. HPS is the most common gastrointestinal disease in the first few weeks of life. Case presentations: Two patient: a girl, 2 month old (aterm baby) and a boy, 2 months old (preterm baby) with diagnosis moderate dehydration ec vomiting, suspect HPS. Both patient got recurrent vomiting since 1 week before admission, and got dehydration, The vomiting was projectile, occuring after the patient was drink the formula milk. We found the olive sign in both patients, but it was not an obligation we should find olive sign, because it just found in 70% patients of HPS. In these patients were found sunken eyes, and slow return turgor that indicating dehydration. Patients were got Ultrasonography and planned for barium meal examination and Ph monitoring. These patients was undergone pyloromyotomi for definite therapy. After surgery preterm baby was still vomiting for 2-3 days in preterm baby, but not in aterm baby. Conclusion: HPS in preterm baby got more complications after surgery than aterm baby, such as: longer length of stay, reflux post operative.